Analysis Of Factors Related To Posyandu Activity In The Covid-19 Era In Pematang Pelintahan Village - Nurhamida Fithri (JURNAL KEBIDANAN KESTRA (JKK), 2021)
During the Covid-19 pandemic, the social conditions of the community connected with health services for infants and toddlers, including posyandu activities. The routine implementation of the posyandu is neglected, including monitoring the growth and development of infants and toddlers and immunization coverage. This is because all services and health are focused on Covid-19. The initial survey conducted in Pelintahan Village, there were 9 posyandu and there was a decline in the implementation of the posyandu program during the Covid-19 pandemic. In addition, the report on immunization coverage also appears to be decreasing. To analyze the factors that relate to the activity of posyandu in the Covid-19 era in Pelintahan Village in 2021. This study used an analytical research design using a cross sectional approach. The population in this study were all mothers who have toddlers in Pelintahan Village as many as 59 people. The sample size in this study used the accidental sampling technique. The sample was taken when posyandu activities in Pelintahan Village took place during the time the research took place and amounted to 36 people. Data analysis in this study used the chi-square statistical test. The results of the study found that there was a significant relationship between maternal anxiety and family support for posyandu activities in the Covid-19 era in Pelintahan Village in 2021 with each p-value of 0.00 (p-value <0.05). From the results of this study, it is expected that health workers can provide health education to mothers and families who have babies and toddlers providing health promotion, counseling and counseling related to safe posyandu during the Covid-19 pandemic.